Wernicke–Korsakoff syndrome in a patient with self-neglect associated with severe depression. (3rd February 2014) - Cocksedge, Karen A; Flynn, Adrian
Lesson: Wernicke–Korsakoff syndrome is a neuropsychiatric disorder resulting from thiamine deficiency and commonly associated with chronic alcoholism, but we describe the first case report resulting from self-neglect associated with depression.